2014
DOI: 10.1007/s10753-014-9878-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Serum IL-12 and IL-18 are Associated with Lower Frequencies of CD4+CD25highFOXP3+ Regulatory T cells in Young Patients with Type 1 Diabetes

Abstract: Type 1 diabetes is thought to involve chronic inflammation, which is manifested by the activation and expression of different inflammatory mediators. IL-12 and IL-18 are two cytokines that have been shown to exert strong proinflammatory activity and have been implicated in the pathogenesis of type 1 diabetes in mice and humans. The overproduction of proinflammatory mediators is controlled by specialized T cell subset, namely regulatory T cells that express FOXP3 transcription factor. Since IL-12 and IL-18 medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 59 publications
6
34
0
Order By: Relevance
“…We performed ELISA assays on the plasma from these populations to analyze IL-18 levels. Confirming previous reports in adults and children [14, 26], we found that IL-18 is significantly increased in the sera of juvenile T1Ds compared to controls (p=0.0391; Figure 1A). Importantly, to determine if outliers were skewing the data toward a significant result, we also performed a ROUT test (Q=0.5%), to remove outliers.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We performed ELISA assays on the plasma from these populations to analyze IL-18 levels. Confirming previous reports in adults and children [14, 26], we found that IL-18 is significantly increased in the sera of juvenile T1Ds compared to controls (p=0.0391; Figure 1A). Importantly, to determine if outliers were skewing the data toward a significant result, we also performed a ROUT test (Q=0.5%), to remove outliers.…”
Section: Resultssupporting
confidence: 92%
“…Corroborating other reports [14, 24-26], we show a significant increase in the concentration of IL-18 in the serum of T1D patients compared to the control group. We also analyzed IL-18BP and IL-37 levels in these patients.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, IL-12 levels were negatively correlated with the size of the Treg population [72]. Moreover, human beta cells were identified as an important target of IL-12 in T1D and IL-12-induced beta cell dysfunction, namely reduced insulin secretion in response to glucose stimulation, could be observed [73].…”
Section: Page 17 Of 33mentioning
confidence: 99%
“…The ratios are shown (f). *P < 0.05; **P < 0.01; ***P < 0.001 d i a b e t e s , a n d p s o r i a s i s a n d h a v e f o u n d t h a t CD4 + CD25 + FoxP3 + Treg numbers were profoundly decreased in patients with active disease [19][20][21][22][23]. Previous studies on bone marrow failure syndromes revealed a decrease in the CD4…”
Section: Discussionmentioning
confidence: 99%